Software database design and management method - Muminov B. B.; Bekmurodov U.B. (Research Parks Publishers, 2021)
Cleverly communication frameworks had four modules of the computer program suite with a disseminated computing handle based on communication scenarios. In these modules, database administration hones have been created to create or select tables, table metadata, sorts, properties, and occasions based on database plan, administration, and IDEF1x models